Productive and reproductive performance of Saanen goat at AZZahra farm of Sandakan in Malaysia (Bangladesh Journal of Animal Science, 2018)
An experiment was conducted at AZ-Zahra Farm, Sandakan, Sabah, Malaysia to investigate the productive and reproductive performance of Saanen dairy goat. Body weight at different ages were collected once while birth weight was collected when does gave birth. On the other hand, milk production of each individual per day was received continuously for three months. The data on reproductive parameters such as length of estrus cycle, duration of estrus period, age at puberty, gestation length, age at first kidding, litter size, birth weight and kid mortality were noted. Descriptive statistics such as number, percentage, mean, standard deviation were performed. T-test was also conducted to know the statistical difference between the groups. Result demonstrated that body weight increases significantly (p